Chick embryos have the same pattern of hypoxic lower‐brain activation as fetal mammals. Issue 1 (11th June 2015) - Landry, Jeremy P.; Hawkins, Connor; Lee, Aaron; Coté, Alexandra; Balaban, Evan; Pompeiano, Maria
ABSTRACT: cFos expression (indicating a particular kind of neuronal activation) was examined in embryonic day (E) 18 chick embryos after exposure to 4 h of either normoxia (21% O2 ), modest hypoxia (15% O2 ), or medium hypoxia (10% O2 ). Eight regions of the brainstem and hypothalamus were surveyed, including seven previously shown to respond to hypoxia in late‐gestation mammalian fetuses (Breen et al., 1997; Nitsos and Walker, 1999b). Hypoxia‐related changes in chick embryo brain activation mirrored those found in fetal mammals with the exception of the medullary Raphe, which showed decreased hypoxic activation, compared with no change in mammals. This difference may be explained by the greater anapyrexic responses of chick embryos relative to mammalian fetuses. Activation in the A1/C1 region was examined in more detail to ascertain whether an O2 ‐sensitive subpopulation of these cells containing heme oxygenase 2 (HMOX2) may drive hypoxic brain responses before the maturation of peripheral O2 ‐sensing. HMOX2‐positive and ‐negative catecholaminergic cells and interdigitating noncatecholaminergic HMOX2‐positive cells all showed significant changes in cFos expression to hypoxia, with larger population responses seen in the catecholaminergic cells. Hypoxia‐induced activation of lower‐brain regions studied here was significantly better correlated with activation of the nucleus of the solitary tract (NTS) than with that of HMOX2‐containing A1/C1 neurons. Together, these observations suggest that (1) the functional circuitry controlling prenatal brain responses to hypoxia is strongly conserved between birds and mammals, and (2) NTS neurons are a more dominant driving force for prenatal hypoxic cFos brain responses than O2 ‐sensing A1/C1 neurons. © 2015 Wiley Periodicals, Inc. Develop Neurobiol 76: 64–74, 2016